2017
DOI: 10.1111/cmi.12753
|View full text |Cite
|
Sign up to set email alerts
|

Expression patterns of sterol transporters NPC1 and NPC2 in the cnidarian-dinoflagellate symbiosis

Abstract: The symbiotic interaction between cnidarians (e.g., corals and sea anemones) and photosynthetic dinoflagellates of the genus Symbiodinium is triggered by both host-symbiont recognition processes and metabolic exchange between the 2 partners. The molecular communication is crucial for homeostatic regulation of the symbiosis, both under normal conditions and during stresses that further lead to symbiosis collapse. It is therefore important to identify and fully characterise the key players of this intimate inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
39
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 73 publications
2
39
1
Order By: Relevance
“…Aiptasia has proven to be a powerful emerging tool for the genetic and molecular study of the cnidarian—alga symbiosis (Sunagawa et al, 2009 ; Thornhill et al, 2013 ; Voolstra, 2013 ; Baumgarten et al, 2015 ; Bellis et al, 2016 ; Dani et al, 2017 ; Matthews et al, 2017 ). Beyond these realms, only a few studies have begun to exploit the advantages Aiptasia has to offer (Tolleter et al, 2013 ; Starzak et al, 2014 ; Leal et al, 2015 ; Biquand et al, 2017 ; Gegner et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Aiptasia has proven to be a powerful emerging tool for the genetic and molecular study of the cnidarian—alga symbiosis (Sunagawa et al, 2009 ; Thornhill et al, 2013 ; Voolstra, 2013 ; Baumgarten et al, 2015 ; Bellis et al, 2016 ; Dani et al, 2017 ; Matthews et al, 2017 ). Beyond these realms, only a few studies have begun to exploit the advantages Aiptasia has to offer (Tolleter et al, 2013 ; Starzak et al, 2014 ; Leal et al, 2015 ; Biquand et al, 2017 ; Gegner et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…An example is the mTOR modulator TSC2, which also regulates the GTPase activity of Rab5 (Chen, Cheng, Hong, & Fang, ; Jiang & Yeung, ; Xiao, Shoarinejad, Jin, Golemis, & Yeung, ). Rab5 is an important modulator of endo‐/phagocytosis and was previously shown to localize at the symbiosome in Aiptasia, potentially conferring the characteristics of an arrested phagosome (Chen et al, ; Dani et al, ; Venn et al, ). The microtubule‐associated protein DYN1 was phosphorylated near the mammalian phosphosite Ser774‐p.…”
Section: Discussionmentioning
confidence: 99%
“…is an important modulator of endo-/phagocytosis and was previously shown to localize at the symbiosome in Aiptasia, potentially conferring the characteristics of an arrested phagosome (Chen et al, 2004;Dani et al, 2017;Venn et al, 2009). The microtubule-associated protein DYN1 was phosphorylated near the mammalian phosphosite Ser774-p. Richter et al (2018) recently showed that phosphorylation at Ser774-p modulates the binding of DYN1 to the vesicular glutamate transporter 1 (VGLUT1) and to endophilin, hence regulating the intracellular trafficking of glutamate-containing vesicles.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the interaction of miRNAs with the mRNAs for FGFR, TGFβR and components of the TNFR/TRAF pathways (Figure ) is particularly intriguing, as these proteins were previously suggested to be involved in the priming of immune and stress responses of symbiotic cnidarians, pathways that might have been co‐opted during the evolution of mechanisms allowing a stable endosymbiosis (Barshis et al., ; Detournay et al., ). In addition, proteins that localize to the symbiosome membrane are thought to be critical for the establishment and/or maintenance of the endosymbiosis, including proteins involved in symbiosome maturation (Chen, Cheng, Hong, & Fang, ; Chen, Cheng, Sung, Kuo, & Fang, ) and in cross‐membrane nutrient exchange (Dani, Ganot, Priouzeau, Furla, & Sabourault, ; Dani et al., ; Lehnert et al., ). In this context, we also identified miRNA‐interacting mRNAs that encode proteins that are likely to be involved in the maintenance of the symbiosome, including a homolog of LAMP1, a protein related to lysosome—and potentially symbiosome—trafficking and maturation (Mohamed et al., ); a homolog of the sterol transporter NPC1 (Dani et al., , ; Ganot et al., ; Lehnert et al., ); and a homolog of the peptide transporter ABCB9 (Davy et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, proteins that localize to the symbiosome membrane are thought to be critical for the establishment and/or maintenance of the endosymbiosis, including proteins involved in symbiosome maturation (Chen, Cheng, Hong, & Fang, 2004;Chen, Cheng, Sung, Kuo, & Fang, 2003) and in cross-membrane nutrient exchange (Dani, Ganot, Priouzeau, Furla, & Sabourault, 2014;Dani et al, 2017;Lehnert et al, 2014). In this context, we also identified miRNA-interacting mRNAs that encode proteins that are likely to be involved in the maintenance of the symbiosome, including a homolog of LAMP1, a protein related to lysosome-and potentially symbiosome-trafficking and maturation (Mohamed et al, 2016); a homolog of the sterol transporter NPC1 (Dani et al, 2014(Dani et al, , 2017Ganot et al, 2011;Lehnert et al, 2014); and a homolog of the peptide transporter ABCB9 (Davy et al, 2012). Of note, LAMP1 and NPC1 mRNA levels were reduced in symbiotic anemones, perhaps reflecting the binding of their regulatory miRNAs and arguing for a repressive effect in these particular cases (Table S4).…”
Section: Discussionmentioning
confidence: 99%